(2 + 2) Cycloaddition products of zirconium and hafnium hydrazinediides with allenes and heteroallenes and their thermally induced rearrangements - Gehrmann, Thorsten; Plundrich, Gudrun; Wadepohl, Hubert; Gade, Lutz H. (Organometallics, 2012)
Reactions of the hydrazinediido complexes [M(N2TBSNpy)(NNPh2)(py)] (M = Zr (1a), Hf (1b)) with (hetero)allenes result in a variety of [2 + 2] cycloaddition products of the general type [M(N2TBSNpy)(κ2N,E-(E(═E′R)NNPh2)(py)] (E = CH2, S; E′ = CH, N; R = alkyl, aryl). The reaction of [Zr(N2TBSNpy)(NNPh2)(py)] (1a) with 1 molar equiv of phenyl or mesityl isothiocyanate at room temperature yields [Zr(N2TBSNpy)(κ2N,S-SC(═NAr)NNPh2)(py)] (Ar = phenyl (2a), mesityl (2b)). Reacting the hydrazinediides [M(N2TBSNpy)(NNPh2)(py)] (M = Zr (1a), Hf (1b)) with allenes results in the formation of the metallaazacyclobutanes [M(N2TBSNpy)(κ2N,C-N(NPh2)CH2C═CH(R))(py)] (M = Zr, R = Ph (4a), cyclohexyl (5a), methyl (6); M = Hf, R = phenyl (4b), cyclohexyl (5b)). Subsequent heating of the cycloaddition products revealed different reactivity patterns: the complex [Zr(N2TBSNpy)(κ2N,S-SC(═NAr)NNPh2)(py)] (2a) forms the isomerization product [Zr(N2TBSNpy)(κ2N,S-SC(═NNPh2))NPh] (3), retaining the N-N bond of the hydrazide. In contrast, the metallacyclobutanes 4a,b and 5a,b show a tendency toward N-N bond cleavage, resulting in the formation of the C-N- and C-C-coupled product complexes [M(κ4N,N,N,N-N2TBSNpyNC(Me)═CHCy)(NPh2)] (M = Zr (7a), Hf (7b)), [Zr(N2TBSNpy)(κ2N,C-(Ph)NC6H4C(Me)═C(Ph)NH)] (8) and [Zr(κ4N,N,N,N-N2TBSNpyNC(Me)=CHPh)(NPh2)] (9).
Gesehen am 17.05.2018
Im Text steht [2 + 2]